Caracterização do desenvolvimento e funcionalidade das crianças expostas ao vírus Zika no período pré-natal no município de Belo Horizonte - Ana Luísa Pereira Cardoso de Rezende (2022)
Introduction: During the epidemic of infection by the zika virus (ZIKV) that took place in Brazil from 2015 to 2018, an association was established between the infection of pregnant women and the birth of children presenting microcephaly and a spectrum of congenital malformations, called Congenital Zika Virus Syndrome (CZS). The long-term repercussions of prenatal exposure to ZIKV in children with CZS, as well as among those without developmental changes in the first months of life is not yet fully understood. In the city of Belo Horizonte, the dimension of changes in development and functional limitations among children with prenatal exposure to the virus are unknown. Characterizing the repercussions of prenatal exposure to ZIKV on the development and functionality of children can contribute to the understanding of its early and late consequences and help to direct public policies. Objective: To characterize the global development and functionality of children exposed to ZIKV in the prenatal period in the city of Belo Horizonte. Methodology: This is a retrospective cohort study of children residing in Belo Horizonte, in Minas Gerais state, Brazil, who were exposed to ZIKV in the prenatal period during 2016 to 2018 and were monitored by the municipal network of the Unified Health System (SUS). Information regarding the characteristics of pregnancy and peripartum, as well as clinical data and information regarding the children’s development were obtained from the electronic medical record of the Belo Horizonte City Hall Results and discussion: Among the 158 children, 87% (138/158) presented typical development, and 13% (20/158), atypical development; 10% (15/158) with developmental changes identified in the first year of life, including 6 children with CZS, and 3% (5/158) after the first year. Among children with atypical development identified in the first year of life, 40% (6/15) were exposed to ZIKV in the first trimester of pregnancy, and 33% (5/15) in the second trimester. There was a higher frequency of SCZ among children exposed to the virus in the first trimester of pregnancy, with a statistically significant difference (p=0,0012). Congenital impairments were identified in 18% of the sample, with a higher frequency of CNS malformations and all cases of microcephaly among children with atypical development identified in the first year of life. Children whose development was identified as atypical in the first year of life had more severe developmental changes and more disabling functional limitations. Children whose development was considered typical in the first months of life and who presented characteristics of atypical development after this period, showed milder developmental changes, which happened, in some cases, in a transient way and with less or no functional impact. Conclusion: The greatest impact on the functionality of children exposed to ZIKV in Belo Horizonte occurred among those with developmental changes identified in the first year of life, with a greater concentration of the most compromised children among those exposed to the virus in the first trimester of pregnancy. Studies involving face-to-face assessments with standardized assessment instruments are recommended to a more accurately estimate of late changes in development and functionality among asymptomatic children in the first year of life.